BOOSTING READING COMPREHENSION ACHIEVEMENT AND VOCABULARY MASTERY: A QUASI-EXPERIMENTAL DESIGN WITH RAP - Aryanti, Nurul; Ardiansyah, Welly; Rosyidin, Iskandar; Putra, Leonardi Jaye; Meirani, Wasitoh (Department of English Education, Universitas Panca Sakti Bekasi, 2023)
The aim of this research is to ascertain the impact of the RAP reading strategy on the academic progress of pupils in vocabulary and reading comprehension. The sample for this study comprised 45 pupils (22 females and 23 males) from Sriwijaya State Polytechnic who were in their second semester during the 2022-2023 academic year. This research was conducted using a quasi-experimental approach. The study employed a vocabulary test, a reading comprehension test, and the RAP reading strategy. The data analysis used mean, standard deviation, standard error mean, and t-tests for both the vocabulary test and the reading comprehension achievement test. The statistical significance level was set at .05. The study demonstrated that there were significant differences in reading comprehension achievement and vocabulary mastery between the experimental group and the control group. However, the RAP reading strategy was found to be more effective in enhancing reading comprehension achievement and vocabulary mastery than the traditional reading strategy. Overall, the RAP reading strategy can be a valuable tool for improving students' vocabulary and reading comprehension.